PERSEPSI GURU TERHADAP PELAYANAN ADMINISTRATIF PEGAWAI TATA USAHA DI SMP NEGERI KECAMATAN KOTO TANGAH - Reszyi Febriani (Universitas Negeri Padang, 2014)
The goal of this research are to get information about perceptions of teachers to administrative personnel administration services. The population is 302 teachers. And the sample is 60 teachers, that taken by random sampling technique. This research instrument is a question with a Likert scale models that have been tested for validity and reliability. Data were analyzed using the average value. The results of this study are perceptions of teachers to administrative personnel administration services attempt at a junior high school Koto Tangah subdistrict is Good Enough. Kata kunci: pelayanan pegawai tata usaha